2020
DOI: 10.3389/fmars.2020.00117
|View full text |Cite
|
Sign up to set email alerts
|

Comparsion of Activities of Fatty Acyl Desaturases and Elongases Among Six Teleosts With Different Feeding and Ecological Habits

Abstract: Fatty acyl desaturases 2 (Fads2) and elongases of very-long-chain fatty acid 5 (Elovl5) are two key enzymes involved in the biosynthesis of long-chain polyunsaturated fatty acids (LC-PUFAs), and their activities determine the LC-PUFA biosynthetic ability of teleost. In order to investigate the relation of enzymic activities with fish's feeding habits and ecological habits, the activities of Fads2 and Elovl5 were compared among six teleosts, namely, freshwater carnivorous mandarin fish (Siniperca chuatsi), fres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
1
7
1
Order By: Relevance
“…mykiss salmonids showed that fads2, elovl5 and/or elovl2 are highly expressed in liver, intestine and brain (Morais et al, 2009;Abdul Hamid et al, 2016). The expression patterns and activity of desaturases and elongases are influenced by factors such as phylogeny, and ecological and feeding habits (Garrido et al, 2019;Xie et al, 2020). Therefore, results of transcript abundance in different tissues of A. tropicus are in accordance with previous results in freshwater fish species.…”
Section: Discussionsupporting
confidence: 85%
“…mykiss salmonids showed that fads2, elovl5 and/or elovl2 are highly expressed in liver, intestine and brain (Morais et al, 2009;Abdul Hamid et al, 2016). The expression patterns and activity of desaturases and elongases are influenced by factors such as phylogeny, and ecological and feeding habits (Garrido et al, 2019;Xie et al, 2020). Therefore, results of transcript abundance in different tissues of A. tropicus are in accordance with previous results in freshwater fish species.…”
Section: Discussionsupporting
confidence: 85%
“…However, the gene expression in the kidney was the lowest among all the measured tissue, which was inconsistent with the orange-spotted grouper findings [44]. These results suggest that the diversification of fish LC-PUFA synthesis in different tissues could be associated with factors such as feeding habits, ecological habits, and species-specific evolutionary history [45].…”
Section: Discussioncontrasting
confidence: 58%
“…Although high expressions of liver elovl5 and/ or ÎŽ6fad genes were observed in fish fed higher SO level diets, the upregulation of genes related to FA desaturation and elongation did not seem to result in increased EPA and DHA tissue contents; instead, it is the dietary SO substitution level that determines the fate of tissue EPA and DHA levels, which indicates that the ability of the grouper to synthesize n-3 LC-PUFAs is very weak. The FA desaturation and elongation activity vary with the fish species (Xie et al, 2020).…”
Section: Ta B L Ementioning
confidence: 99%
“…In comparison with warm water fish, marine or carnivorous fish are considered to have limited ability to convert linoleic acid (LA) and linolenic acid (LNA) to n-6 and n-3 LC-PUFAs, such as EPA and DHA, owing to the weak activity of fatty acyl desaturases (FADs) (Castro et al, 2016;Xie et al, 2020). Therefore, further studies on the potential use and role of the dietary SO inclusion in marine fish are required to promote the sustainable development of aquaculture.…”
Section: Introductionmentioning
confidence: 99%